1994
DOI: 10.1007/bf00203883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a microplate assay specific for heavy metal toxicity

Abstract: Abstract.A rapid, quantitative microbial assay, which is specific for heavy metal toxicity, has been developed. The assay (MetPLATE TM) is in a 96-well microtitration plate format and is suitable for determining toxicity characteristics such as median inhibitory concentrations. The sensitivity of MetPLATE TM to heavy metals [Cu, Zn, Cd, Pb, Hg, Cr(III)] was generally higher than Microtox and was of the same order as or better than Daphnia and fish bioassay. MetPLATE was insensitive to organic compounds at con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 11 publications
4
54
0
Order By: Relevance
“…Cenci et al (1987) also reported that phenol and some chlorophenols did not inhibit β-galactosidase activity of Escherichia coli even at high concentration. Similar insensitivity of β-galactosidase activity to phenol has also been confirmed through a number of investigations (Bitton et al, 1992a(Bitton et al, , 1992bBitton and Koopman, 1994). Similarly, Barnhart and Vestal (1983) reported that in vitro α-glucosidase activity was relatively insensitive to pentachlorophenol, phenol and sodium dodecylsulphate.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Cenci et al (1987) also reported that phenol and some chlorophenols did not inhibit β-galactosidase activity of Escherichia coli even at high concentration. Similar insensitivity of β-galactosidase activity to phenol has also been confirmed through a number of investigations (Bitton et al, 1992a(Bitton et al, , 1992bBitton and Koopman, 1994). Similarly, Barnhart and Vestal (1983) reported that in vitro α-glucosidase activity was relatively insensitive to pentachlorophenol, phenol and sodium dodecylsulphate.…”
Section: Resultssupporting
confidence: 48%
“…Inhibition of biosynthesis and activity of α-glucosidase and β-galactosidase in bacteria have been used to assess toxicity of inorganic and organic toxicants (Barnhart and Vestal, 1983;Dutton et al, 1988;Dutton et al, 1990;Guven et al, 2003;Bitton and Koopman, 1994;Codina et al, 1994, Nweke and. It was previously reported that bioassay based on α-glucosidase and β-galactosidase activity is insensitive to heavy metals (Barnhart and Vestal, 1983;Dutton et al, 1988Dutton et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…In a MetPLATE ™ assay system (based on β-galactosidase activity), zinc IC 50 of 0.11 ± 0.001 mg/l (0.002mM) was reported for Escherichia coli [5]. In a growth inhibition test assessed via turbidity measurements, 7.15 mg/l Zn 2+ (0.12mM) inhibited the growth of Pseudomonas putida by 50 % [34].…”
Section: +mentioning
confidence: 99%
“…welled METPlate and with E.coli as the indicator species (Bitton, et al, 1994). In the procedure a chromophore buffer was added, followed by a 90 minute incubation period.…”
Section: Chemical and Toxilogic Analysesmentioning
confidence: 99%